Analysis of female demographics in the United States: life expectancy, education, employment, family building decisions, and fertility service utilization. Issue 3 (June 2021) - Esencan, Ecem; Simsek, Burcin; Seli, Emre
Abstract : Purpose of review: To discuss changes in female demographic parameters in the US and associated increase in utilization of fertility services. Recent findings: Fractions of women earning bachelor's, master's, and doctoral degrees increased from 1970 to 2018 (32.6 vs 64.8; 7.9 vs 27.3; 0.54 vs 5.7 per 10, 000 women; P  < .001; respectively). This was associated with decrease in percentage of married women (61.9% vs 50.8%) and increase in median age at first marriage (20.8 vs 27.8). In parallel, mean age of mothers at first birth increased (21.4 vs 26.8), and pregnancy rates of women aged 35–39 and 40–44 years doubled between 1980 and 2010 (0.036 vs 0.077; 0.009 vs 0.019 per 1, 000 women). With later pregnancy attempts, female fertility rates decreased from 1970 to 2017 (87.9% vs 60.3%; P  < .001). Women undergoing assisted reproductive technologies (ART) treatment with a DOR diagnosis increased (12% vs 31%), and ART cycles using donor eggs increased (16, 161 vs 24, 300), between 2005 and 2016. Summary: Participation of women in education is paralleled by increased female employment, later occurrence of marriage, increased age of childbearing, decreased fertility rates, and increased DOR diagnosis.